Pedagogical questions in initial teacher trainning: improvement in education quality - Lamim, Adriele Ribeiro dos Santos; Lamim Netto, Manoel de Souza [UNESP]; Zanon, Dulcimeire Aparecida Volante (Centro Univ Nove Julho, 2022)
Nowadays, concern about education quality has increased considerably in different society dimensions and spaces, expressed through governmental politics and social and educator actions. Bearing in mind that teachers learn from the situations derived from school environment and that they do not only modify them but are also modified by them, it's more and more important to discuss the implications of teacher training on the quality of education. The proposition of an initial formation of teachers based on reflections is an alternative for the qualification and professional development of teachers, because teachers with developed reflexive thoughts can have a bigger set of actions about students, scholar context, teaching, learning and professional development insofar as they look for answers to daily situations that arise, linking them with theories and giving new signification. Intending to contribute to this formative process, this paper presents the use of the Pedagogical Questions contained in the Smyth Cycle as a relevant tool to raise reflections of future teachers about their performance at school, allowing them to analyze, reconstruct and improve the quality of their intervention.
Keywords: Smyth cycle; Chemistry education; Initial teacher training; Reflective teacher; Education quality